Where are Brazil's marine litter scientific data? - Ramos, Bruna de; Lima, Tábata Martins de; Costa, Monica Ferreira da (Frontiers in Sustainability, 2022)
The environmental sciences work with datasets every day. However, the availability of these data in repositories is still new. Records of marine litter from emerging economies are scarce and generally difficult to find, especially in databases. This work reviews and analyzes data repositories to identify the existence of datasets related to marine litter in Brazil. Only one global repository specializing in marine litter was found. It is in the early stages of operation. Only two datasets about marine litter in Brazil were found in the generalist repository Figshare that do not follow all the FAIR principles (Findable, Accessible, Interoperable, and Reusable) for data sharing. A few initiatives are being developed aiming to collect and share marine litter data but only one of them (Our Blue Hands) is already in place and uses a standardized, replicable method, and aims to share the data by design. Our work identified interoperability the main point to be tackled within our context. In the Decade of Ocean Science for Sustainable Development (2021–2030) is essential that repositories are created, improved, and encouraged to ad-dress the specific needs of marine litter data-sharing and researchers’ behavioral shift to start sharing the data already collected. Data sharing allows not only the integrated vi-sion of the academic community but can also contribute to public policies, helping deci-sion-makers and encouraging a more sustainable science regarding financial and natural resources use.